2021
DOI: 10.11591/ijece.v11i1.pp763-771
|View full text |Cite
|
Sign up to set email alerts
|

A short-term hybrid forecasting model for time series electrical-load data using random forest and bidirectional long short-term memory

Abstract: In the presence of the deregulated electric industry, load forecasting is more demanded than ever to ensure the execution of applications such as energy generation, pricing decisions, resource procurement, and infrastructure development. This paper presents a hybrid machine learning model for short-term load forecasting (STLF) by applying random forest and bidirectional long short-term memory to acquire the benefits of both methods. In the experimental evaluation, we used a Bangladeshi electricity consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Many scholars have attempted to predict the electric load in the past, typically using the traditional ANN, time series and other techniques. Researchers used LSTM, Bi-LSTAM and RF-bi-LSTM to forecast the electric load and found that RF-bi-LSTM performed much better based on this statistical mean square error (MSE), mean absolute error (MAE), mean absolute percentage error (MAPE) and root mean square error (RMSE) [20]. The MAPE examination reveals an error of 127 W, which is around 4.1% to 3.2% of the reported range of peak load encountered in a day and is well within the range of meaningful accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Many scholars have attempted to predict the electric load in the past, typically using the traditional ANN, time series and other techniques. Researchers used LSTM, Bi-LSTAM and RF-bi-LSTM to forecast the electric load and found that RF-bi-LSTM performed much better based on this statistical mean square error (MSE), mean absolute error (MAE), mean absolute percentage error (MAPE) and root mean square error (RMSE) [20]. The MAPE examination reveals an error of 127 W, which is around 4.1% to 3.2% of the reported range of peak load encountered in a day and is well within the range of meaningful accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, we used the long-term short-term memory (LSTM) method to estimate the economic impact of the COVID-19 outbreak on different regions of the United States [31,37]. When dealing with time series, we used LSTM modelling, an in-depth learning method that is useful when trying to model time series.…”
Section: -4-1 Long Term Short-term Memorymentioning
confidence: 99%
“…RF is a supervised learning method that is a decision tree-based algorithm. As the name proposes as forest the RF classifier is an ensemble of decision trees wherever a random vector sample produce each classifier from the input vector [28] and every tree cast a unit vote for the most popular class to classify an input vector, nearly all of the time trained with a bagging method.…”
Section: Random Forestmentioning
confidence: 99%